Isometric muscle strength and mobility capacity in children with cerebral palsy. Issue 2 (16th January 2017) - Dallmeijer, Annet J.; Rameckers, Eugene A.; Houdijk, Han; de Groot, Sonja; Scholtes, Vanessa A.; Becher, Jules G.
Abstract: Purpose : To determine the relationship between isometric leg muscle strength and mobility capacity in children with cerebral palsy (CP) compared to typically developing (TD) peers. Method : Participants were 62 children with CP (6–13 years), able to walk with (n = 10) or without ( n = 52) walking aids, and 47 TD children. Isometric muscle strength of five muscle groups of the leg was measured using hand-held dynamometry. Mobility capacity was assessed with the 1-min walk, the 10-m walk, sit-to-stand, lateral-step-up and timed-stair tests. Results : Isometric strength of children with CP was reduced to 36–82% of TD. When adjusted for age and height, the percentage of variance in mobility capacity that was explained by isometric strength of the leg muscles was 21–24% (walking speed), 25% (sit-to-stand), 28% (lateral-step-up) and 35% (timed-stair) in children with CP. Hip abductors and knee flexors had the largest contribution to the explained variance, while knee extensors showed the weakest correlation. Weak or no associations were found between strength and mobility capacity in TD children. Conclusion : Isometric strength, especially hip abductor and knee flexor strength, is moderately related to mobility capacity in children with CP, but not in TD children. To what extent training of these muscle groups will lead to better mobility capacity needs further study. Implications for Rehabilitation: Strength training in children with cerebral palsy (CP) may be targeted more specifically at hip abductors and knee flexors. The moderate associations imply that large improvements in mobility capacity may not be expected when strength increases.